2005
DOI: 10.2302/kjm.54.150
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fatty acid composition in human bone marrow aspirates

Abstract: In the present study, the fatty acid composition of bone marrow aspirates and serum phospholipids in nine patients with hematologic diseases was investigated, and the effect of fatty acids on osteoblast differentiation in ST2 cells was examined. The concentrations of oleic acid and palmitic acid were significantly higher in bone marrow aspirates than in serum phospholipids, but the concentrations of other fatty acids did not differ. The rate of alkaline phosphatase positive ST2 cells induced by BMP2 was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…We found that palmitate and stearate are not only the predominant FA present in the lipotoxic media but also that these two FA significantly affect osteoblast function and survival. Interestingly, these two FA have been shown not only to have a toxic effect on several cell types including hepatocytes [26], beta cells [27] and osteoblasts [30], but also in the particular case of palmitate, it has been reported as one of the most prevalent FA secreted into the bone marrow [31] as well as a potent inducer of apoptosis in osteoblasts [20]. In agreement with previous studies looking at lipotoxicity in other cell models [20, 26], both, palmitate and stearate showed a lipotoxic effect in our model through the induction of apoptotic changes and the activation of caspases 3/7.…”
Section: Discussionmentioning
confidence: 99%
“…We found that palmitate and stearate are not only the predominant FA present in the lipotoxic media but also that these two FA significantly affect osteoblast function and survival. Interestingly, these two FA have been shown not only to have a toxic effect on several cell types including hepatocytes [26], beta cells [27] and osteoblasts [30], but also in the particular case of palmitate, it has been reported as one of the most prevalent FA secreted into the bone marrow [31] as well as a potent inducer of apoptosis in osteoblasts [20]. In agreement with previous studies looking at lipotoxicity in other cell models [20, 26], both, palmitate and stearate showed a lipotoxic effect in our model through the induction of apoptotic changes and the activation of caspases 3/7.…”
Section: Discussionmentioning
confidence: 99%
“…Also, oleic acid but not palmitic acid, increases the rate of alkaline phosphatase positive ST2 cells induced by bone morphogenetic protein-2 [31]. It has been proposed that all these differences may affect osteoblast differentiation in the bone marrow microenvironment [31]. However, the effects of phospholipid fatty acids on osteoblast differentiation are not yet fully understood.…”
Section: Importance Of Dietary Fatty Acids On Phospholipid Distributimentioning
confidence: 99%
“…; 3) In certain cases of leukemia, a shift of low density lipoprotein (LDL) from blood to spleen, liver and bone marrow was observed [14][15]. At the remission, LDL in peripheral blood return to normal values.A drop in saturated and monounsaturated fatty acids in the bone marrow was also described in leukemic patient [16], [17]. The involvement of fatty acids has been widely demonstrated in some cancers such as breast cancer [18][19] but has never been studied in CML.…”
Section: Introductionmentioning
confidence: 99%